Status of native bumble bees (Bombus spp.) at Fort Riley Military Reservation, Kansas - Lathrom, Cassidy (My University, 2025)
Bumble bees (Bombus spp.) serve as essential pollinators of native grassland forbs and agricultural crops, supporting plant reproductive success, maintaining floral diversity, and enhancing ecosystem resilience. Despite their ecological importance, Bombus spp. have experienced substantial declines in abundance and distribution, prompting concerns for pollinator conservation across Great Plains ecosystems, including the tallgrass prairie ecoregion. The ecoregion is home to a suite of six native bumble bee species: American bumble bee (B. pensylvanicus), Southern Plains bumble bee (B. fraternus), Black and Gold bumble bee (B. auricomus), Common Eastern bumble bee (B. impatiens), Brown-Belted bumble bee (B. griseocollis), and Two-spotted bumble bee (B. bimaculatus). Of conservation concern are the Southern Plains bumble bee and American bumble bee, with an estimated 89% population decline over the past 20 years. I assessed Bombus spp. community composition, occurrence, land cover associations, and population density within Fort Riley Military Reservation, Kansas, a key large remnant of the tallgrass prairie ecoregion. My research integrated three objectives to evaluate Bombus spp. populations over time and space by assessing: (1) variation in Bombus spp. diversity and abundance relative to land cover, floral type, and prairie management practices, focusing on Southern Plains bumble bee and American bumble bee; (2) the potential for use of distance sampling to estimate bumble bee density; and (3) local-scale relationships between floral resource availability and Bombus spp. density through capture-mark-recapture methods. Land cover associations were analyzed by performing canonical correspondence analysis (i.e., visualizing relationships among land cover types, management intensity, and bumble bee species abundances). There was separation among species relative to use of land cover types, indicating that Bombus spp. segregate among land cover types on the landscape. I used package Distance in Program R to evaluate the potential to estimate density of Bombus spp. across Fort Riley using distance sampling. Data were comprised of six species, including American bumble bee, Southern Plains bumble bee, Black and Gold bumble bee, Common Eastern bumble bee, Brown-Belted bumble bee, and Two-Spotted bumble bee. I estimated 1.30 Bombus spp./ha (CV = 0.184), 1.40 Bombus spp./ha (CV = 0.122), and 1.80 Bombus spp./ha (CV = 0.108) during 2022, 2023, and 2024, respectively. These results indicate that distance sampling can be used to estimate Bombus spp. density in the tallgrass prairie and serve as a baseline for future assessments. Over three field seasons (2022–2024), a total of 15,596 individual bumble bees were captured and marked across 44 unique sampling sites representing all six native Bombus species. Across these sites, 37 unique floral colonies (i.e., dense patches of nectaring flowers for bumble bee foraging habitat) were identified: 10 in 2022, 18 in 2023, and 9 in 2024. Among these, five dominant floral types were most frequently observed across years and sample bouts: tall thistle (Cirsium altissimum), roundhead prairie clover (Dalea multiflora), wild bergamot (Monarda fistulosa), partridge pea (Chamaecrista fasciculata), and milkweed (Asclepias spp.). Three bumble bee species accounted for >80% of all captures: Brown-belted bumble bee (5,618 individuals; 36%), Black and Gold bumble bee (3,826; 25%), and American bumble bee (3,412; 22%). Southern Plains bumble bee comprised 13% of total abundance, while Two-spotted and Common Eastern bumble bees each represented just 2% of individuals captured. Site-level species richness remained consistently high across years and bouts, ranging from 4 to 6 species per site (mean ± SD = 5.0 ± 0.4), indicating strong community diversity and persistence of all six species on Fort Riley across years. Results provide baseline data for future monitoring efforts and support compliance with federal conservation mandates under the Sikes Act of 1960 and the 1973 Endangered Species Act, should species of concern be listed.
Keywords: Bombus; Bumble bee